7 - Political Representation in Africa: Towards a Conceptual Framework - Edigheji, Omano (Africa Development, 2006)
Political representation as a central component of democratic governance is a key challenge in the African quest for democratic development. Accordingly, this article reviews theories of political representation. On the basis of the re- view and subsequent critique of existing theories, I suggest some areas that require attention from African scholars, civil society, political leaders and policy- makers. I argue that the responsiveness of the political system and public policy to the needs and aspirations of the African people would be considerably de- pendent on an inclusive system that gives ordinary people a voice in govern- ance and policy choices.